Nanotechnology in drug delivery: the need for more cell culture based studies in screening - Kura, Aminu Umar; Fakurazi, Sharida; Hussein, Mohd. Zobir; Arulselvan, Palanisamy (Chemistry Central, 2014)
Advances in biomedical science are leading to upsurge synthesis of nanodelivery systems for drug delivery. The systems were characterized by controlled, targeted and sustained drug delivery ability. Humans are the target of these systems, hence, animals whose systems resembles humans were used to predict outcome. Thus, increasing costs in money and time, plus ethical concerns over animal usage. However, with consideration and planning in experimental conditions, in vitro pharmacological studies of the nanodelivery can mimic the in vivo system. This can function as a simple method to investigate the effect of such materials without endangering animals especially at screening phase.